Peran Pemerintah Daerah Dalam Implementasi Hak Kekayaan Intelektual Guna Melindungi Dan Mempromosikan Batik Banten - Purwaningsih, Endang; Santosa, Irwan; Salim, Nabila (Lembaga Penelitian Universitas YARSI, 2025)
This study aims to analyze (1) the role of local governments and related institutions in the area in the implementation of IPR in efforts to promote and protect Banten's special batik; and (2) the implementation of the above stakeholders' roles on Banten batik works and solutions to their constraint factors. This research is included in normative juridical research which emphasizes secondary data supported by interviews with informants. The research results show the role of Local Governments and Related Provincial Offices in Banten in the implementation of IPR in efforts to promote and protect Banten's special batik based on assessments on craftsmen and Banten batik owners needs to be improved as their interests in batik production to upscale. The implementation of stakeholders' roles on Banten batik works and solutions to their constraint factors has been quite good so far, however, the expectations of the artisans need to be enhanced along with the aspirations of Banten batik business actors